Mapping Climate-Agriculture-Gender Inequity Hotspots to Build Resilience - Mishra, Avni; Lecoutere, Els; Puskur, Ranjitha; Koo, Jawoo; Azzarri, Carlo (AgriLinks, 2022)
In many cases, women are more vulnerable to adverse climate change impacts, due to their limited asset ownership, such as land, as well as more reduced access to capital, labor and agricultural inputs. Women also have more limited access to information, which, in turn, means lower awareness and knowledge of climate risks and strategies to manage them. Social norms and gender roles in many countries limit women’s participation in strategic decision-making in their households and communities, making them less able to participate in and affect group activities, access extension services or adopt new practices and technologies. Overall, their capacity to respond to climate stress is lower.